2014
DOI: 10.1021/ie4031314
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Silver Nanoparticle Formation in a Microreactor: Reaction Kinetics Coupled with Population Balance Model and Fluid Dynamics

Abstract: Reactive kinetics coupled with population balance model (PBM) and computational fluid dynamics (CFD) was implemented to simulate silver nanoparticles (AgNPs) formation in a microtubular reactor. The quadrature method of moments, multiphase model theory, and kinetic theory of granular flow were employed to solve the model, and the particle size distributions (PSD) were calculated. The simulation results were validated by synthesizing AgNPs experimentally in an actual microtubular reactor for comparison with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…183 The preferential adsorption of citrate ions on Ag(111) faces resulted in the preferential growth of other crystal faces while the protective components in the foliar broth could cause the formation of the cracking and stacking up of the petals. 187 The model and its applicability in predicting formation and particle size distribution of Ag NPs in the continuous-flow tubular system were subsequently validated. WA simple and rapid biological approach was recently disclosed to synthesize water-soluble and highly roughened ''meatball''-like Au NPs using green tea extract under microwave irradiation.…”
Section: Plant-mediated Synthesismentioning
confidence: 99%
“…183 The preferential adsorption of citrate ions on Ag(111) faces resulted in the preferential growth of other crystal faces while the protective components in the foliar broth could cause the formation of the cracking and stacking up of the petals. 187 The model and its applicability in predicting formation and particle size distribution of Ag NPs in the continuous-flow tubular system were subsequently validated. WA simple and rapid biological approach was recently disclosed to synthesize water-soluble and highly roughened ''meatball''-like Au NPs using green tea extract under microwave irradiation.…”
Section: Plant-mediated Synthesismentioning
confidence: 99%
“…However, to the best of our knowledge, green synthesis of AuAg bimetallic NPs utilizing biosynthesis with plants and microorganisms in a microreactor has been little reported hitherto. In our earlier studies, it was demonstrated that AgNPs could be continuously synthesized by combining plant-mediated bioreduction and continuous-flow microreactor (Huang et al 2008;Liu et al 2012Liu et al , 2014. Here, we extended the rapid and green protocol to the synthesis of Au-Ag bimetallic NPs in a microreactor using C. Platycladi extract as both reductant and a stabilizer, the reductive mechanism of C. Platycladi extract has already been explored by our group (Huang et al 2011).…”
Section: Introductionmentioning
confidence: 98%
“…It is difficult to implement microfluidic chips because the nanoparticle formation process involves nucleation, growth, aggregation, and breakage in liquid–solid two‐phase mixtures. In addition, the simulation of nanoparticle formation in a microfluidic biosynthesis process (liquid–solid system), a novel field, lacks appropriate reaction kinetics data . In some reports, a population balance equation (PBE) was employed as a method for predicting particle and crystal evolution, which could calculate the nucleation, growth, aggregation, and breakage process appropriately.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the simulation of nanoparticle formation in a microfluidic biosynthesis process (liquid-solid system), a novel field, lacks appropriate reaction kinetics data. 23 In some reports, a population balance equation (PBE) was employed as a method for predicting particle and crystal evolution, 24 years. 30 -35 In this work, by taking respective advantages into consideration, a CFD-PBM (population balance model) coupled model was established to describe PtNPs formation in the microfluidic chip.…”
Section: Introductionmentioning
confidence: 99%